Sport-specific yearly risk and incidence of anterior cruciate ligament tears in high school athletes - Gornitzky, A. L.; Lott, A.; Yellin, J. L.; Fabricant, P. D.; Lawrence, J. T.; Ganley, T. J. (The American Journal of Sports Medicine, 2016)
Background: Anterior cruciate ligament (ACL) injury rates are affected by frequency and level of competition, sex, and sport. To date, no study has sought to quantify sport-specific yearly risk for ACL tears in the high school (HS) athlete by sex and sport played. Purpose: To establish evidence-based incidence and yearly risk of ACL tears in HS athletes by sex for sports performed at the varsity level across the majority of US high schools. Study Design: Meta-analysis. Methods: PubMed, EMBASE, and Cochrane Central Register of Controlled Trials were searched to identify all articles reporting ACL tears per athletic exposure in HS athletes. ACL injury incidence rates (IRs) by sex and sport were calculated via meta-analysis. State athletic association guidelines were used to determine the number of exposures per season to calculate yearly risk of ACL tears. Results: The search recovered 3779 unique articles, of which 10 met our inclusion criteria, for a total of 700 ACL injuries in 11,239,029 exposures. The IR was 0.062 injuries per 1000 exposures (95% CI, 0.058-0.067). Although more injuries were recorded in males than females, females had a higher rate of injury per exposure (relative risk, 1.57; 95% CI, 1.35-1.82). Relative risk was highest in basketball (3.80; 95% CI, 2.53-5.85) and soccer (3.67; 95% CI, 2.61-5.27). While boys` football had the highest number of ACL injuries at 273, girls` soccer had the highest IR (0.148; 95% CI, 0.128-0.172). In girls, the highest injury risks per season were observed in soccer (1.11%; 95% CI, 0.96%-1.29%), basketball (0.88%; 95% CI, 0.71%-1.06%), and lacrosse (0.53%; 95% CI, 0.19%-1.15%). In comparison, the highest risks for boys were observed in football (0.80%; 95% CI, 0.71%-0.91%), lacrosse (0.44%; 95% CI, 0.18%-0.90%), and soccer (0.30%; 95% CI, 0.22%-0.41%). Conclusion: There is an approximately 1.6-fold greater rate of ACL tears per athletic exposure in HS female athletes than males. However, there is significant risk in both sexes, particularly in high-risk sports such as soccer, football, basketball, and lacrosse. Knowledge of sport-specific risk is essential for future injury reduction programs, parent-athlete decision making, and accurate physician counseling.